Income tax (International), 2019 reissue - Krishna, Vern; Khirdaji, Nada (Halsbury's Laws of Canada ; [v.53R], 2019)
Canada imposes taxes based on taxpayer residence and on the source of income, and the rules relating to this international taxation are complex. This title presents a straightforward and lucid explanation of those rules, and how they are applied by the taxing authorities.